Incongruencias jurídicas respecto al procedimiento de la partición de bienes hereditarios, que afectan a la seguridad jurídica de los ecuatorianos garantizada en el art.82 de la Constitución de la República del Ecuador - Castro León, Jammie Dayanna (2022)
Not everything ends with death, thus, inheritance law is as old as property itself, with the term succession from the Latin: sucessio, designating all cases in which a change or substitution of one or more subjects in a legal relationship can be produced by virtue of a transmission; according to our Civil Code, assignments by cause of death are those made by law or the will of a deceased person to succeed to the property of the deceased. Succession Law is constituted by legal rules that are in charge of regulating the patrimony of a person after his death, who will be succeeded by his heirs or legatees, for which our legislation establishes three forms of distribution of the partitionable mass, among which is the extrajudicial partition which is carried out before a notary public who is in charge of solemnizing the partition of hereditary goods according to the attribution given in Art. 18, numeral 37 of the Notary Law. This attribution does not provide full legal certainty, since within the aforementioned article, due to the simplification of the procedure, it is mentioned that only the petition must be presented, plus the recognition of signatures and the documents that prove the assets of the deceased, without mentioning that the inventory of the deceased's assets should be added as a mandatory requirement in order to ensure that there are no presumed damages for the presumed heirs.